El Boletín de Acción Católica de la Mujer de la Junta Diocesana de Córdoba (1932) - Sánchez Blanco, Laura (Cauriensia, 2022)
In this study, an analysis of the content of the Bulletin of "Catholic Action of Women" is carried out, which was published by the Diocesan Board of Córdoba in 1932, to know the type of writings that were disseminated during the Republican Government, in defense of Catholicism Social. The ten localized issues of the Bulletin are digitized in the Virtual Library of Historical Press and are very useful for providing new data to the history of Catholic Action.